Knowledge Regarding Risk Factors of Phlebitis and its Association with Education Among Nurses at Tertiary Care Hospital, Karachi: Knowledge Regarding Risk Factors of Phlebitis - Bibi, Afsha; Ali, Mahboob; Pervaiz, Sadia; Mary, Shiza; Mary, Misheal; Bagga, Sabir; Khalid, Samson; Ahmad khan, Rasheed; Sami, Abdul; Khan, Raheem (Pakistan Journal of Health Sciences, 2023)
Phlebitis is the inflammation of a vein, typically in the legs, due to a blood clot or other causes. Risk factors for developing phlebitis include prolonged immobility, age, family history, obesity, smoking, and certain medical conditions, such as cancer, heart disease, and inflammatory bowel disease, which can increase the risk of phlebitis. Objective: To assess the knowledge regarding risk factors of phlebitis and its association with nurses’ education among nurses at a tertiary care Hospital in Karachi. Methods: This cross-sectional analytical study was conducted at a tertiary care hospital in Karachi from September to December 2022. A total of 53 nurses were part of the study, and a convenient sampling technique was used to approach the participants. The data were collected through a valid and reliable tool. Results: Study results show that Among 53 participants, the male participant 26(49.1%), whereas the female participant was 27 (50.9%). Study results also found that 17.0% of nurses have High-level knowledge, whereas 83.0% of the participants have moderate, level knowledge about the risk factors of phlebitis. Moreover, the study found no significant difference between the knowledge score and the nurses' education p-value of 0.794. Conclusions: These findings suggest that nurses may need further education and training regarding the risk factors of phlebitis, as most nurses have only a moderate level of knowledge. Investigating other factors impacting nurses’ knowledge may also be essential, such as work experience and training programs.